Going for the Gold : Quantifying and Ranking Visual Night Sky Quality in International Dark Sky Places - John Barentine (International Journal of Sustainable Lighting, 2016)
Since the invention of electric lighting in the nineteenth century, the steadily increasing use of artificial light at night in outdoor spaces has grown to threaten the integrity of dark night skies and nocturnal terrestrial spaces. The conservation community has gradually come to accept the need to protect natural nighttime darkness, which finds expression in dark sky parks and similar protected areas. As these places begin to reap tangible economic benefits in the form of sustainable ‘astrotourism,’ the movement to actively protect them gains strength. The International Dark-Sky Association designates Dark Sky Parks and Reserves under a comparative ranking scheme that assigns night sky quality tiers according to a combination of objective and subjective characteristics, but shortcomings in the consistency of these ratings exist that undermine the consistency and reputation of the designation program. Here we consider potential changes to the qualification regime to make the ratings system more robust for the benefit of future designations.